2012
DOI: 10.1097/bot.0b013e318225f793
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Stabilization System (LISS) Versus Proximal Femoral Nail Anti-rotation (PFNA) in Treating Proximal Femoral Fractures

Abstract: Therapeutic Level II. See page 128 for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
1
26
1
Order By: Relevance
“…They can be done by minimally invasive methods. Clinical studies have also shown good or equivalent results of reverse-DFLCP compared to intramedullary devices [15][16][17]26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be done by minimally invasive methods. Clinical studies have also shown good or equivalent results of reverse-DFLCP compared to intramedullary devices [15][16][17]26].…”
Section: Discussionmentioning
confidence: 99%
“…But they are associated with a higher number of varus collapse and implant failure [13,14]. To overcome this problem the reverse-DFLCP of the contralateral side has been advocated by some authors, as it provides an added number of screw options for proximal femoral fracture fragment, resulting in a more stable construct [15][16][17]. They are anatomically suitable for proximal femoral fractures because the shape of the lateral condyle of the femur is similar to the greater trochanter, and the plate of the contralateral side follows the physical curve of the femoral shaft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrophic nonunion was observed in all cases. An appropriate-length distal femoral LISS plate was chosen using a right-sided plate for the left femur and vice versa, and placed as previously described after the reduction of the nonunion was confirmed using an image intensifier, with minor modifications [20]. In brief, the plate was placed close to the proximal and the posterior of the femur in order to fix the proximal of the nonunion and the vastus lateralis was split for it is convenient to place plate under direct version.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The Less Invasive Stabilization System for the treatment of distal femurs (LISS-DF, Synthes USA, Paoli, PA) was designed as an optimized fixation for fractures of the knee [17][18][19]. 'upside-down' LISS, so-called reverse LISS, has been successfully employed to treat complex proximal femur fractures [20][21][22][23][24][25]. However, combined procedure of modified FVFG and reverse LISS in the treatment of femoral neck nonunion has not been described so far.…”
Section: Introductionmentioning
confidence: 99%